Arylpyrrolyldiketone Boron Complexes Exhibiting Various Anion‐Binding Modes Based on Dynamic Conformation Changes. Issue 10 (29th August 2018) - Kuno, Atsuko; Fujiwara, Masaya; Haketa, Yohei; Maeda, Hiromitsu
Abstract: Arylpyrrolyldiketone boron complexes as anion‐responsive π‐electronic molecules were synthesized by Claisen condensations of acetylpyrrole and corresponding aryl esters. The synthesized π‐electronic molecules exhibited anion‐binding behavior with various binding modes including pyrrole‐inverted and non‐inverted [1+1]‐type anion complexes as well as [2+1]‐type complexes owing to the presence of only a single pyrrole ring. Furthermore, solid‐state ion‐pairing assemblies, comprising receptor–anion complexes and countercations, were constructed based on fairly planar [2+1]‐type complexes. Abstract : Pair up ! Arylpyrrolyldiketone boron complexes synthesized by Claisen condensations exhibited anion‐binding behavior with various binding modes including pyrrole‐inverted and non‐inverted [1+1]‐type anion complexes as well as [2+1]‐type complexes owing to the presence of only a single pyrrole ring (see figure).